Haplotype-Based noninvasive prenatal diagnosis for duchenne muscular dystrophy: A pilot study in South China. (September 2019) - Chen, Min; Chen, Chao; Li, Yingting; Yuan, Yuan; Lai, Zhengfei; Guo, Fengyu; Wang, Yaoshen; Huang, Xiaoyan; Li, Shiquan; Wu, Renhua; Peng, Zhiyu; Sun, Jun; et al.
Abstract: Objective: To explore the accuracy and feasibility of noninvasive prenatal diagnosis (NIPD) for Duchenne Muscular Dystrophy (DMD) based on the haplotype approach. Methods: We recruited singleton pregnancies at-risk of DMD at 12–25 weeks of gestation from 17 families who all had a proband child affected by DMD. We have identified the pathogenic mutations in probands and their mothers by multiplex ligation-dependent probe amplification (MLPA). To construct parental haplotypes, we performed captured sequencing on genomic DNA from parents and probands. The integration analysis of parental haplotypes and targeted sequencing results of maternal plasma DNA were used to infer the fetal haplotype and genotypes in the DMD gene. Fetal DMD genotypes were further confirmed by invasive prenatal diagnosis. Result: We have successfully performed the haplotype-based NIPD in all recruited families. Ten fetuses were identified as normal, including four female and six male fetuses. Four female fetuses were carriers, and the other three male fetuses were affected by DMD with exons 49–52 deletion, exons 8–37 deletion and c.628 G > T mutation, respectively. The results of NIPD were consistent with those of invasive diagnosis. Conclusion: Haplotype-based NIPD for DMD by targeted sequencing is promising and has the potential for clinical application.